2022
DOI: 10.1039/d2fo00723a
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens seed oil combined with Anredera cordifolia leaf powder attenuates age-related cognitive decline by reducing serum triglyceride and glucose levels in healthy elderly Japanese individuals: a possible supplement for brain health

Abstract: Supplementation of PO + AC for 12-month improved cognitive function in healthy Japanese elderly, presumably by lowering serum triglyceride, blood glucose and N-(epsilon)-carboxymethyl-lysine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The characteristics of the included studies are presented in Table 1 . A total of 158 rat models and five studies [ 22 , 23 , 24 , 25 , 26 ] were included in the meta-analysis, while other studies were excluded mainly because the statistical analyses were not informative when using insufficient data. For the purpose of this meta-analysis, we evaluated the therapeutic effects of Perilla frutescens on animal models that were mentioned at least twice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are presented in Table 1 . A total of 158 rat models and five studies [ 22 , 23 , 24 , 25 , 26 ] were included in the meta-analysis, while other studies were excluded mainly because the statistical analyses were not informative when using insufficient data. For the purpose of this meta-analysis, we evaluated the therapeutic effects of Perilla frutescens on animal models that were mentioned at least twice.…”
Section: Resultsmentioning
confidence: 99%
“…Although these effects resulted from the analysis of in vitro and in vivo studies, there were few clinical trials that outlined significant therapeutic effects for human subjects. Attenuation of age-related cognitive decline, antiallergic, antioxidant, prokinetic, and antispasmodic effects are among the proven therapeutic proprieties of Perilla frutescens in these studies [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that clinical investigations into the utilization of DHA, EPA, N-3 and PUFAs have become prevalent. 219–222 In recent years, a 12-week double-blind study was conducted to examine the effects of egg yolk choline intake (a key component of lecithin) on cognitive functions in aged males and females, which suggested that continued 300 mg day −1 intake of egg yolk choline could enhance verbal memory. 223 SCFAs, especially butyric acid, are considered important nutritional factors in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Perilla frutescens seeds oil (PO) administration alone or in conjunction with Anredera cordifolia leaf (AC) powder was tested for its influence on cognitive performance in healthy Japanese seniors in a randomized, double-blind, parallel-armed intervention experiment [ 87 ]. Participants were randomly assigned to receive either 1.47 mL of PO per day or a combination of 1.47 mL of PO and 1.12 g of AC powder per day.…”
Section: Antioxidant and Hypolipemiant Effectsmentioning
confidence: 99%